MODELA DBT: Model-driven elaboration language applied to dynamic binary translation - Salgado, Filipe Alexandre Andrade (2017)
Industrial solutions design is a highly complex topic due to the challenge of integrating multiple technologies into a single solution, the inherent complexity of the problems to be solved and also because the proposed solutions often require a great level of interoperability among their components and also the outside world. Dynamic Binary Translation has been used as a tool to deal with such interoperability issues, e.g., legacy support, virtualization and secure execution, among others. However its integration in the industry as an end-product is hampered by the intricate variability management required in this subject. To address these issues and in an attempt to power DBT utilization as an interoperability-providing tool, we propose a model-driven DSL modeling language for DBT architectures. The developed DSL proved to be efficient to model an in-house DBT engine, and MODELA DBT, a framework for ready-to-use DBT solutions was obtained. MODELA DBT provides design validation, easy configuration of customizable DBT parameters and components, as well as code generation features.